2011
DOI: 10.1021/ef101678s
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Catalysis of Liquid-Phase Hydroperoxide Decomposition in Hydrocarbons

Abstract: The autoxidation of jet fuel takes place via a complex free radical reaction mechanism that involves the decomposition of hydroperoxides.The liquid-phase, unimolecular decomposition of hydroperoxide has been isolated for experimental study. Three hydroperoxides relevant to jet fuel autoxidation, including cumene hydroperoxide (CHP), dodecane hydroperoxide (DHP), and ethylbenzene hydroperoxide (EBHP), were thermally decomposed separately and found to closely fit first-order behavior with respect to hydroperoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…The oxidation rate of trimethylbenzenes has been observed to follow the order 1,2,3 > 1,2,4 > 1,3,5-trimethylbenzene [19,20]. This supports our observations of lower stability of 1,2,4 vs 1,3,5-trimethylbenzene based on oxygen induction times [21]. This appears to be related to the number of adjacent methyl pairs versus unreactive isolated methyl pairs as discussed by Silva [22].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The oxidation rate of trimethylbenzenes has been observed to follow the order 1,2,3 > 1,2,4 > 1,3,5-trimethylbenzene [19,20]. This supports our observations of lower stability of 1,2,4 vs 1,3,5-trimethylbenzene based on oxygen induction times [21]. This appears to be related to the number of adjacent methyl pairs versus unreactive isolated methyl pairs as discussed by Silva [22].…”
Section: Resultssupporting
confidence: 76%
“…Ethylbenzene was found to produce hydroperoxides at lower temperatures than dodecane highlighting that benzylic hydrogens on alkyl aromatics are more reactive than paraffinic hydrogens. Zabarnick's work found that in jet fuels the oxidation pathways are mainly due to alkyl aromatic oxidation and that the normal approximate 80% concentration of paraffins in jet fuel can be considered unreactive with respect to peroxy radical reactions [21,25]. Zabarnick's work highlights the importance of understanding oxidation of potential single component aromatic blending components.…”
Section: Resultsmentioning
confidence: 99%
“…Organic hydroperoxides are formed and decomposed during the oxidation of organic compounds by molecular oxygen, which is the leading source of concern for the air stability of food, gasoline, plastics and other organic materials . For this reason, decomposition of organic hydroperoxides has been addressed in a large number of reports, all of which have clearly indicated the high complexity of the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown the importance and role of oxygen-containing heteroatoms, such as phenols and hydroperoxides, in fuel autoxidative thermal stability . Phenols have been shown to inhibit oxidation but increase surface and bulk deposit formation. , Hydroperoxides are primary autoxidation products at relatively low temperatures (<120 °C) and rate-controlling reaction intermediates at higher temperatures (≥140 °C). , Some sulfur-containing species (e.g., mercaptans, sulfides, disulfides, thiophenes, and benzothiophenes) have been shown to be detrimental to fuel thermal stability. Nitrogen species (e.g., indoles, anilines, quinolines, amines, pyridines, carbazoles, and indolines) have been studied less frequently with conflicting results; some nitrogen species greatly increase deposition while others are relatively innocuous. Most previous model fuel studies considered heteroatomic species in isolation rather than as mixtures of heteroatomic species classes, as occurs in actual fuels. A relatively small number of studies have explored the interaction between heteroatomic species during fuel autoxidation. …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Hydroperoxides are primary autoxidation products at relatively low temperatures (<120 °C) and ratecontrolling reaction intermediates at higher temperatures (≥140 °C). 4,5 Some sulfur-containing species (e.g., mercaptans, sulfides, disulfides, thiophenes, and benzothiophenes) have been shown to be detrimental to fuel thermal stability. 6−9 Nitrogen species (e.g., indoles, anilines, quinolines, amines, pyridines, carbazoles, and indolines) have been studied less frequently with conflicting results; some nitrogen species greatly increase deposition while others are relatively innocuous.…”
Section: ■ Introductionmentioning
confidence: 99%